Cycloastragenol Attenuates Osteoclastogenesis and Bone Loss by Targeting RANKL-Induced Nrf2/Keap1/ARE, NF-κB, Calcium, and NFATc1 Pathways - Wang, Gang; Ma, Chao; Chen, Kai; Wang, Ziyi; Qiu, Heng; Chen, Delong; He, Jianbo; Zhang, Cheng; Guo, Ding; Lai, Boyong; Zhang, Shuangxiao; Huang, Linfeng; et al. (Frontiers in Pharmacology, 2022)
Osteoporosis, which typically affects postmenopausal women, is an osteolytic disease due to over-activation of osteoclasts. However, current drugs targeting osteoclast inhibition face various side effects, making natural compounds with great interest as alternative treatment options. Cycloastragenol (CAG) is a triterpenoid with multiple biological activities. Previously, CAG’s activity against aging-related osteoporosis was reported, but the mechanisms of actions for the activities were not understood. This study demonstrated that CAG dose-dependently inhibited osteoclast formation in receptor activator of nuclear factor-κB ligand (RANKL)-stimulated bone marrow macrophage (BMMs). Mechanism studies showed that CAG inhibited NF-κB, calcium, and nuclear factor of activated T cells 1 (NFATc1) pathways. Additionally, CAG also promoted the nuclear factor-erythroid 2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1)/anti-oxidative response element (ARE) pathway that scavenges reactive oxygen species (ROS). Furthermore, CAG was also found to prevent bone loss of postmenopausal osteoporosis (PMO) in a preclinical model of ovariectomized (OVX) mice. Collectively, our research confirms that CAG inhibits the formation and function of osteoclasts by regulating RANKL-induced intracellular signaling pathways, which may represent a promising alternative for the therapy of osteoclast-related disease.